A comparison of pop and chop to divide and conquer in resident cataract surgery - Gross FJ (Dove Medical Press, 2016)
Fredric J Gross, Debra E Garcia-Zalisnak, Courtney E Bovee, Joy D Strawn Department of Ophthalmology, Eastern Virginia Medical School, Norfolk, VA, USA Abstract: In this randomized prospective study, the cumulative dissipated energy and case time of pop and chop and of traditional four-quadrant divide and conquer in the first 60 cases (in total 120 eyes) of cataract surgery performed by two residents at the Veterans Administration Hospital in Hampton, Virginia, were compared. Overall and individually, the residents had significantly shorter case times and used significantly less cumulative dissipated energy for performing pop and chop than that for divide and conquer technique. There was no difference in complication rates or visual outcomes between these two techniques. The results of this study suggest that pop and chop is a more time- and energy-efficient method of nucleofractis than divide and conquer for novice resident surgeons. Keywords: case time, cataract surgery, phacoemulsification, cumulative dissipated energy